Analysis of the decay chain of the nucleus 293117. (29th October 2015) - Sobiczewski, A
Abstract: The decay chains of the nucleus 293 117 observed recently at JINR-Dubna are analyzed theoretically. The α -transition energies, the α -decay and the spontaneous-fission half-lives, and, are studied. The analysis of the α decay uses a phenomenological model based on the assumption that the decay goes between the states of the same structure. The calculations are performed in three variants using masses obtained within three nuclear-mass models accurately describing masses of heaviest nuclei. The experimental are reproduced with the average discrepancies: 260, 280 and 310 keV, in the considered three variants. The measured are reconstructed with the average ratios: 3.3, 4.4 and 5.4 in these variants.